Psychology around us - Comer, Ronald J.; Gould, Elizabeth, 1962- (Hoboken, N.J. : Wiley, 2012)
"Comer and Gould's Psychology Around Us demonstrates the many-often surprising, always fascinating-intersections of psychology with students' day-to-day lives. Every chapter includes sections on human development, brain function, individual differences and abnormal psychology that occur in that area. These "cut-across" sections highlight how the different fields of psychology are connected to each other and how they connect to everyday life.Every chapter begins with a vignette that shows the power of psychology in understanding a whole range of human behavior. This theme is reinforced throughout the chapter in boxed readings and margin notes that celebrate the extraordinary processes that make the everyday possible and make psychology both meaningful and relevant. The text presents psychology as a unified field the understanding of which flows from connecting its multiple subfields and reinforces the fact that psychology is a science with all that this implies (research methodology, cutting edge studies, the application of critical thinking). "--
Machine generated contents note: Chapter 1: Psychology: Yesterday and TodayChapter 2: Psychology As a ScienceChapter 3: Human DevelopmentChapter 4: NeuroscienceChapter 5: Sensation and PerceptionChapter 6: ConsciousnessChapter 7: LearningChapter 8: MemoryChapter 9: Language and ThoughtChapter 10: IntelligenceChapter 11: MotivationChapter 12: Emotion, Stress, and HealthChapter 13: PersonalityChapter 14: Social PsychologyChapter 15: Psychological DisordersChapter 16: Treatment of Psychological Disorders.
Includes bibliographical references.
Keywords: Psychology -- Textbooks; PSYCHOLOGY / General